Effectiveness of spiramycin for treatment of congenital Toxoplasma gondii infection in rhesus monkeys. - Schoondermark-Van de Ven, E (1994)
The effectiveness of spiramycin for the treatment of rhesus monkey fetuses congenitally infected with Toxoplasma gondii was studied. Eight monkeys were infected at day 90 of pregnancy. This is comparable to the second trimester of organogenetic development in humans. Transmission of infection was found prenatally in five of the eight monkeys by detection of the parasite in the amniotic fluid. Treatment with spiramycin (20 mg/kg/day in two intermittent doses given intravenously) was started as soon as fetal infection was proven and was continued until birth. Nine to 14 days after initiation of treatment, the parasite was still detectable in amniotic fluid samples from four of these five cases. However, the parasite was detected only by PCR and not by mouse inoculation. T. gondii was also detected only by PCR in the placenta of one monkey that delivered prematurely. This monkey received spiramycin treatment for only 2 weeks. In the four monkeys that received treatment for about 7 weeks, the parasite was not present at birth in the placenta nor in amniotic fluid or neonatal organs. Spiramycin accumulates mainly in maternal tissues. Although concentrations in neonatal tissue were found to be 5 to 28 times higher than the corresponding concentrations in neonatal serum, the concentrations in neonatal tissue were still 11 to 16 times lower than those found in the mothers. However, no spiramycin was found in the fetal brains. Early treatment with spiramycin may prevent transmission of infection to the fetus but most probably cannot interrupt an existing brain infection, which is the most severe outcome of congenital toxoplasmosis in humans.